The addition of pineapple flesh and pineapple peels extracts to increase the quality of used cooking oil. (April 2018) - Kusumawardani, R; Hasanah, N; Sukemi,
Abstract: In Indonesia, reuse of cooking oil is high and common. Heating process and reuse of the cooking oil causes a change in its chemical constituents and decrease its qualities. This research aimed to investigate the addition of pineapple flesh extract (PFE) and pineapple peel extract (PPE) on the increment of the quality of oxidized (used) cooking oil. The cooking oil has been used three times. Treatment was done by mixing the used cooking oil with the extract (2:1) at 50°C. Peroxide value, FFA and iodine number of treated and untreated used cooking oils were measured by using titration method. The result showed that the treatment could increase the quality of the used cooking oils. PPE was better than PFE to increase the quality of the used cooking oil.